Studi Komparasi Sensor Kelembapan Tanah Menggunakan ESP32 - Bavitra; Leo Anaris Sakti; Dimas Saputra; Zaki Ihwan; Baharudin; Muhammad Abiyyu Alharits (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Soil moisture is a crucial factor in agriculture that affects plant growth and crop productivity. In modern agricultural systems, accurate soil moisture monitoring is essential for optimizing water usage and enhancing the efficiency of automatic irrigation systems. This study aims to develop an Internet of Things (IoT)-based soil moisture monitoring system and evaluate the performance of three types of soil moisture sensors: Soil Moisture FC-28, Capacitive Soil Moisture Sensor, and Soil Moisture Hygrometer Module Sensor. The evaluation compares the accuracy and effectiveness of each sensor in measuring soil moisture. The research methodology involves measuring soil moisture in ten different soil samples using the three sensors simultaneously. The system is based on the ESP32 microcontroller, where data from the sensors are processed and displayed on an LCD Liquid Crystal I2C 20x4. Data analysis is conducted using the one-way ANOVA statistical method to determine whether there are significant differences among the measurement results of the three sensors.The results indicate that each sensor exhibits different measurement characteristics based on its working principle. The Soil Moisture FC-28 sensor, which operates on resistance, shows high sensitivity to changes in soil moisture but is susceptible to corrosion. The Capacitive Soil Moisture Sensor is more durable as it does not have direct contact with the soil, yet it requires more precise calibration. Meanwhile, the Soil Moisture Hygrometer Module Sensor provides more stable results under various environmental conditions. The one-way ANOVA analysis reveals no significant differences in the measurement results among the three sensors.